Combating inequality : rethinking government's role - Blanchard, Olivier (Olivier J.); Rodrik, Dani (Cambridge, Massachusetts : The MIT Press, 2021)
"Edited collection with contributions from notable economists on policy solutions to the problem of economic inequality in advanced economies"--
OCLC-licensed vendor bibliographic record.
Keywords: elektronické knihy; electronic books; Income distribution -- Government policy; Equality -- Economic aspects; Equality -- Government policy; ECONOMICS/Labor Studies; ECONOMICS/Political Economy; ECONOMICS/General